Comparison of Efficacy of Single Dose Tranexamic Acid versus Placebo before Surgery in Females Undergoing Surgery for Ovarian Cancer - Naz, Sadia; Zahoor, Sadia (Indus Journal of Bioscience Research, 2025)
Objective: To compare the efficacy of single-dose tranexamic acid versus placebo in reducing transfusion requirements and perioperative blood loss in females undergoing surgery for ovarian cancer. Methods: This randomized controlled trial was conducted in the Department of Obstetrics and Gynecology, Sheikh Zayed Hospital and Medical College, Rahim Yar Khan, over a 6-month period (December 2024 to May 2025). A total of 372 women aged 18–60 years with ovarian cancer of FIGO stage I–III and ASA class I–III were enrolled and randomized into two groups. Group A (n=186) received tranexamic acid 15 mg/kg intravenously before surgery, while Group B (n=186) received placebo. The primary outcome was efficacy, defined as no postoperative transfusion requirement. Results: All 372 patients completed the study. Baseline characteristics were comparable between groups (p >0.05). The requirement for transfusion was significantly lower in the tranexamic acid group (29.6%) compared to placebo (44.1%) (p=0.003). Efficacy was achieved in 70.4% of patients in the tranexamic acid group versus 55.9% in the placebo group (p=0.003). Mean perioperative blood loss was markedly reduced in the tranexamic acid group (548.3 ± 198.7 ml) compared to placebo (692.1 ± 242.6 ml) (p<0.001). Postoperative hemoglobin levels were significantly higher in the tranexamic acid group (10.2 ± 1.4 g/dl) compared to placebo (9.6 ± 1.6 g/dl) (p=0.001), with a smaller mean hemoglobin decline (1.6 ± 0.8 g/dl vs. 2.3 ± 1.2 g/dl, p<0.001). Conclusion: Single-dose tranexamic acid administered preoperatively significantly reduced transfusion requirements, perioperative blood loss, and hemoglobin decline in ovarian cancer surgery, supporting its use as an effective adjunct in perioperative management.